Evolução molecular da família gênica dos receptores de odores e proteínas ligantes a feromônios e genética de populações de genes quimiossensoriais em espécies de Anastrepha do grupo fraterculus - Rojas Gallardo, Diana Marcela (2016)
This dissertation is divided into three chapters. In the first chapter, we provide a concise literature review that discusses key theoretical concepts, the rationale, and main objectives outlined for this study. The second chapter investigates the molecular evolution of the gene family of odor receptors (ORs) identified in the transcriptomes of two species of fruit flies of great economic importance: Anastrepha fraterculus and A. obliqua. The results showed a high percentage of average identities between ORs from these species, as well as recent gene expansions with signs of positive selection. A comparison of rates of synonymous and nonsynonymous substitutions among Anastrepha species detected evidence of positive selection in the gene Or7c, which is associated to an important potential role in aggregation behavior and host choice for oviposition in D. melanogaster. The third chapter investigates patterns of molecular evolution in pheromone binding proteins (PBPs), also identified in A. fraterculus and A. obliqua, as well as studied pattern of polymorphisms, divergence and populational structure of four chemosensory genes amplified in four species of tephritid flies of fraterculus group: A. fraterculus, A. obliqua, A. sororcula and A. turpiniae. This study contrasted previously identified genes with evidence of positive and purifying selection in order to investigate whether they are contributing to the differentiation among some of the species of this group. We found no evidence of positive selection in PBPs studied in a more global comparison, although we found positive selection signals in some of the genes and studied strains. Population analysis of chemosensory genes in different species of Anastrepha detected high levels of intraspecific nucleotide and haplotype diversity. Divergence tests showed that A. obliqua is the most different species of the ones here investigated, having, in general, high levels of nucleotide substitutions, non-synonymous divergence, as well as fixed species specific differences, whereas we failed to find similar differences amongst the other species here studied. The genes Obp28a, Or7c and Or7d were differentiated in A. obliqua, indicating a potential role in the differentiation of other species in the group, or in this species’ diversification and adaptation.